Effect of camel milk on lipid profile among patients with diabetes: a systematic review, meta-analysis, and meta-regression of randomized controlled trials - Narmin Khalid; Dana N. Abdelrahim; Nivine Hanach; Refat AlKurd; Moien Khan; Lana Mahrous; Hadia Radwan; Farah Naja; Mohamed Madkour; Khaled Obaideen; Husam Khraiwesh; MoezAlIslam Faris (BMC, 2023)
Abstract The effects of camel milk (CM) intake on lipid profile among patients with diabetes remain controversial. This systematic review and meta-analysis of randomized controlled trials (RCTs) aimed to calculate the effect size of CM intake on blood lipids among patients with type 1 (T1D) and type 2 (T2D) diabetes. We searched nine databases from inception until December 31, 2022, to identify relevant RCTs. Effect sizes for total cholesterol (TC), triglycerides (TG), low-density lipoprotein (LDL), very low-density lipoprotein (VLDL), and high-density lipoprotein (HDL) were calculated and expressed using mean differences (MD) and confidence intervals (CI). Of 4,054 retrieved articles, 10 RCTs (a total of 347 participants aged 8-70 years, 60.5% male) were eligible for inclusion. The pooled results from a random-effects model showed statistically significant decreases in TC (MD − 21.69, 95% CI: 41.05, − 2.33; p = 0.03; I 2=99%), TG (MD − 19.79, 95% CI: −36.16, − 3.42; p=0.02, I 2=99%), and LDL (MD −11.92, CI: −20.57, −3.26; p = 0.007, I 2=88%), and a significant increase in HDL (MD 10.37, 95% CI, 1.90, 18.84; p=0.02, I 2=95%) in patients with diabetes supplemented with CM compared with usual care alone. Subgroup analysis revealed that only long-term interventions (> 6 months) elicited a significant reduction in TC levels and TG levels. Consumption of fresh CM by patients with diabetes resulted in significant reductions in TC, TG, and LDL levels, while showing a significant increase in HDL levels. Patients with T1D elicited a more beneficial effect in lowering TC, LDL, and TG levels and in increasing HDL levels than their corresponding partners with T2D. In conclusion, long-term consumption of CM for patients with diabetes, especially those with T1D, could be a useful adjuvant therapy to improve lipid profile alongside prescribed medications. However, the high heterogeneity in the included studies suggests that more RCTs with larger sample sizes and longer intervention durations are required to improve the robustness of the available evidence.